Character Building of Environmental Care on Students in Sekolah Indonesia Kota Kinabalu (SIKK) Malaysia - Masturoh, Masturoh; Ridlo, Saiful (FMIPA UNNES, 2020)
Environmental condition has become increasingly fragile in recent decades. Concern for the environment can help restore environmental condition. Therefore, environmental care is a character that must be implemented by school at each educational level. Sekolah Indonesia Kota Kinabalu (SIKK) has functioned as the center point and become the main/coordinator school for education service Indonesian children in Sabah, Malaysia. It was supposed that people of SIKK become the role model and example for them who take on education in a community learning center in the whole Sabah and Serawak, Malaysia in building the character of environmental care on students.This research aimed to describe the way of character building of environmental care on student in SIKK, Malaysia. This study is a case study which focuses on the way of character building of environmental care on student in SIKK, Malaysia. The data collection uses interviews, observation, and documentation. Then, tested using triangulation process.The result shows that SIKK has made policy which is related to environmental care, made a habit of caring for the environment, held various activities which is related to environmental care, and giving appropriate proponent facilities for character building of environmental care. Yet, still there are some factors which impede the process of student character building on environmental care in SIKK among internal factor in the form of student awareness, and external factor in the form of family factor and surrounding people.Based on the explanation, it can be concluded that SIKK has made an effort to instill the character of caring for the environment in various ways. The obstacle factor in student character building on environmental care included internal factor and external factor. Inhibiting factors can be overcome by positive reinforcement of the teacher toward students and holding monitoring and evaluation meetings related to the development of student behavior together with parents of students.